Turbulence and the characteristics of circumstellar discs - Riaz, Rafeel; Schleicher, D. R. G.; Vanaverbeke, S; Klessen, Ralf S.; Saavedra-Bastidas, J. (Monthly notices of the Royal Astronomical Society, 2024)
We investigate the properties of circumstellar discs (CDs) produced in hydrodynamical simulations of gravoturbulent core collapse considering Kolmogorov and Burger-type turbulence. We report that massive discs are more prevalent in the Kolmogorov regime than for Burger-type turbulence. A signiﬁcant number of discs are formed with a radius of ∼15 au in both cases. However, the number of extended discs with radii >15 au is signiﬁcantly larger in case of Kolmogorov turbulence. The two regimes of turbulence, in general, yield disc radii in the ranges of 7−30 au and 13−39 au, respectively. The corresponding ranges of the disc masses are 30.37 MJup−0.92 M and 2.09 MJup−0.13 M , respectively. Moreover, the ratio Mdisc/Mstar is higher in models of Kolmogorov-type turbulence than in models of Burgers-type turbulence. We do not ﬁnd any correlation between Rdisc and Mdisc over the explored range of initial temperatures (8−14 K) and the type of turbulence. Also, for these initial thermal variations, the turbulent CD structures do not exhibit signs of turbulent diffusion. Nonetheless, both sub- and supersonic velocity dispersions cause variations in the speciﬁc angular momentum of infalling gas, especially for CDs with radii ∼ 16−21 au. The radial proﬁles of CDs do not correlate with the initial conditions.